THE NEED TO DEVELOP THE CONCEPTS OF ACTIVE CITIZENSHIP IN YOUNG STUDENTS' MINDS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, the need to inculcate in the minds of the young generation the concept of citizen, citizenship and active citizenship position, the need to feel and develop feelings of love for the Motherland, loyalty to the country, duty, obligation and responsibility before the country.